ChemInform Abstract: Amino Acid and Water‐Driven Tunable Green Protocol to Access S—S/C—S Bonds via Aerobic Oxidative Coupling and Hydrothiolation. Issue 8 (February 2015) - Shard, Amit; Kumar, Rajesh; Saima, Saima; Sharma, Nidhi; Sinha, Arun K.
Abstract The catalytic system L‐arginine/water in the presence or absence of oxygen allows the synthesis either of disulfides such as (II) and (IV) or of vinyl sulfides of type (VII)/(VIII).